Psychomotor-activating effects mediated by dopamine D(2) and D(3) receptors in the nucleus accumbens. - Canales, J; Iversen, S (2000)
The contribution made by specific dopamine receptor subtypes to the induction of motor behaviors has not been firmly established. Here, we first characterized the behavioral effects induced by a D(2)-class receptor agonist, bromocriptine, following injections into the nucleus accumbens (Acb). Bromocriptine showed an atypical D(2)-class receptor agonist profile, having no observable effect on a range of motor behaviors. However, when coadministered with the D(1)-class receptor agonist SKF 38393, bromocriptine showed a typical D(2)-class receptor agonist profile, enhancing locomotor activity and suppressing spontaneous yawning. We then administered the dopamine receptor antagonists L-741626 and nafadotride, which possess relative selectivity for D(2) and D(3) receptors, respectively, prior to injections of dopamine agonists into the Acb. Nafadotride significantly reduced the locomotor-enhancing effects elicited by the coadministration of SKF 38393 and the D(2)-class receptor agonist (+)-PD 128907 into the Acb, and also attenuated the effects induced by the combination of SKF 38393 and bromocriptine, although not significantly so. L-741626 mildly attenuated the locomotor effects elicited by both drug combinations. Taken together, these results suggest that both D(2) and D(3) receptors in the Acb contribute to the expression of heightened psychomotor activation.